Cybersecurity culture in Portuguese organizations: An exploratory analysis - Cardoso, M. G. M. S.; Laureano, R. D.; Serrão, C. (2017 12th Iberian Conference on Information Systems and Technologies (CISTI), 2017)
Cybersecurity is currently one of the hottest topics for millions of organizations around the world. They depend on information technology to conduct their business processes that are exposed to wide range of security threats, and Portuguese organizations are no exception. How are these organizations taking a holistic approach to allow them to face and handle those threats with confidence? Are the proper technical mechanisms being put in place and are the appropriate information security skills and awareness programs implemented internally? How is all of this being handled by Portuguese organizations? This are some of the questions tackled on a survey addressed to directors of Portuguese organizations in order to map their current cybersecurity culture and corresponding processes.